The Life of General Lord Rawlinson of Trent - Edited by Maurice, Frederick, Maj.-Gen. Sir (London Cassell and Company, Ltd., 1928)
Maj.-Gen. Sir Frederick Maurice's biography.
Include Map, Illustrations, Appendices and Index.
The Life of General Lord Rawlinson of Trent from His Journals and Letters.
Keywords: World War (1914-1918) -- Great Britain -- Rawlinson, Henry Seymour Rawlinson, Baron, 1864-1925 -- Generals